Quelle critique pour l’enseignement du droit ? - Rafael Encinas de Munagorri (Clio@Themis)
In this text, I have tried to point out some critical approaches of legal education and legal teaching in the years 1970-1985, adding personal comments of my own experience as student and professor of law in French universities.